Improving the Knowledge and Attitudes of Pulmonary Tuberculosis Prevention in the Probolinggo Community with Counseling and the Use Of Sobat-TB - Haykal, Muhammad Nazhif; Eljatin, Dwinka Syafira; Putri, Atina Irani Wira; Karimah, Rumman; Fitriani, Fatimah Nur; Putra, Gumilar Fardhani Ami; Hidayah, Rizka Nurul; Fadhlina, Afia Nuzila; Fatmasari, Hindana; Widodo, Aulia Febrianti; Sakina, Sakina (Indonesian Journal of Global Health Research, 2024)
Tuberculosis (TB) is a significant global health issue, particularly in Indonesia. The increasing number of TB cases and deaths highlights the need for health education to reduce the incidence of TB and support eradication efforts. Objective: This study aimed to analyze the knowledge and attitudes of the Probolinggo community toward preventing pulmonary TB through counseling and the use of the Sobat-TB. Method: An analytical observational study with a cross-sectional approach was conducted. The knowledge and attitudes of 50 voluntary respondents were measured using a validated and reliable questionnaire before and after health education interventions, which included counseling, educational videos, and an introduction to the Sobat TB app. The data were analyzed descriptively and statistically at the 95% confidence level. Results: In the Puskesmas Kanigaran area, the initial findings showed poor knowledge and attitudes toward TB prevention among respondents. Postintervention, there was a significant improvement: 46 out of 50 respondents had good knowledge, and 48 out of 50 had positive attitudes toward TB prevention. Statistical analysis confirmed a significant relationship between pre- and postintervention knowledge and attitudes (p=0.0001). Conclusions: Enhanced access to information and continuous health education using modern technology are crucial for achieving TB elimination goals.